Clay encapsulated Cu(OH)(x) promoted homocoupling of arylboronic acids: an efficient and eco-friendly protocol - Dar, Bashir Ahmad; Singh, Snehil; Pandey, Nalini; Singh, A. P.; Sharma, Priti; Lazar, Anish; Sharma, Meena; Vishwakarma, Ram A.; Singh, Baldev (Applied Catalysis A-General, 2014)
Cu(OH)(x) has been encapsulated over montmorillonite-KSF by simple ologomeric deposition strategy. The resulting catalyst has been employed for selective homocoupling of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst is easy to recover and shows excellent reusability without losing its activity. Techniques like XRD, SEM, TPR, IR, BET surface area measurement and XPS were used to characterize the catalyst. The present method promises for the simple and clean homocoupling of arylboronic acids. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Biaryls; clay; Copper; Heterogenous catalyst; Homocoupling